2022
DOI: 10.1212/wnl.0000000000200012
|View full text |Cite
|
Sign up to set email alerts
|

Association of Periodic Limb Movements With Medication Classes

Abstract: Objective:To investigate the association between various medication classes and the periodic limb movement index (PLMI) in a clinical cohort of adults who completed in-laboratory polysomnography.Methods:A single, diagnostic, overnight, in-laboratory polysomnogram was completed for 3,488 patients consecutively referred from 2010-2015 to determine the PLMI. Medication use and medical comorbidities were collected through patient questionnaires. Associations between medication classes and the PLMI were ascertained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 52 publications
0
0
0
Order By: Relevance
“…Those results were expected as SSNRIs are known to delay REM sleep latency and increase N1 sleep duration in subjects without sleep disorders 50 , 51 . Our results also showed that IH patients using antidepressants had higher micro-arousal and PLMS indices than both controls and other IH participants, which can indicate a more fragmented sleep, which is concordant with observations that SSNRIs can impair sleep continuity and increase PLMS 50 , 52 . Since IH participants using antidepressants were mainly women, those results are in line with the findings of Plante 8 , where women with IH had worse sleep efficiency compared to healthy women.…”
Section: Discussionsupporting
confidence: 91%
“…Those results were expected as SSNRIs are known to delay REM sleep latency and increase N1 sleep duration in subjects without sleep disorders 50 , 51 . Our results also showed that IH patients using antidepressants had higher micro-arousal and PLMS indices than both controls and other IH participants, which can indicate a more fragmented sleep, which is concordant with observations that SSNRIs can impair sleep continuity and increase PLMS 50 , 52 . Since IH participants using antidepressants were mainly women, those results are in line with the findings of Plante 8 , where women with IH had worse sleep efficiency compared to healthy women.…”
Section: Discussionsupporting
confidence: 91%